Biocatalytic Synthesis of Quercetin 3‐O‐Glucoside‐7‐O‐Rhamnoside by Metabolic Engineering of Escherichia coli. Issue 18 (6th November 2013) - Roepke, Jonathon; Bozzo, Gale G.
<x xml:space="preserve">Abstract</x> You are what you eat: Quercetin 3‐O‐glucoside‐7‐O‐rhamnoside is a rare natural product with potential biological importance. We describe a strategy for the regioselective synthesis of this bisglycoside by feeding quercetin 3‐O‐glucoside, a naturally abundant precursor, to metabolically engineered Escherichia coli.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>